2021
DOI: 10.1051/0004-6361/202140436
|View full text |Cite
|
Sign up to set email alerts
|

CAPOS: The bulge Cluster APOgee Survey

Abstract: Context. Bulge globular clusters (BGCs) are exceptional tracers of the formation and chemodynamical evolution of this oldest Galactic component. However, until now, observational difficulties have prevented us from taking full advantage of these powerful Galactic archeological tools. Aims. CAPOS, the bulge Cluster APOgee Survey, addresses this key topic by observing a large number of BGCs, most of which have only been poorly studied previously. Even their most basic parameters, such as metallicity, [α/Fe], and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 144 publications
(221 reference statements)
0
6
0
Order By: Relevance
“…8) NGC 6540 (Djorg 3) is a compact cluster that is located toward the Galactic bulge, with literature distances varying between d e = 3-5.3 kpc. The Harris (1996) [Fe/H] value for the cluster is −1.35 but literature estimates tend to vary considerably between −1.01 and −1.5 (Vulic et al 2018;Geisler et al 2021). NGC 6540 was assumed to be an open cluster until Bica et al (1994) confirmed its identity as a GC, with an extended blue HB.…”
Section: Ngc 6453 (Figurementioning
confidence: 99%
“…8) NGC 6540 (Djorg 3) is a compact cluster that is located toward the Galactic bulge, with literature distances varying between d e = 3-5.3 kpc. The Harris (1996) [Fe/H] value for the cluster is −1.35 but literature estimates tend to vary considerably between −1.01 and −1.5 (Vulic et al 2018;Geisler et al 2021). NGC 6540 was assumed to be an open cluster until Bica et al (1994) confirmed its identity as a GC, with an extended blue HB.…”
Section: Ngc 6453 (Figurementioning
confidence: 99%
“…Figure 12 shows a more compact PM distribution for stars within the cluster area with respect to those in the comparison field, suggesting a cohesive structure. As most bulge GCs, Minni 48 follows the local bulge stellar content (Geisler et al 2021;Minniti et al 2021a,b)…”
Section: Colour-magnitude Diagramsmentioning
confidence: 98%
“…One hindrance in being able to draw connections between inner Galaxy GCs and place this population into context with Milky Way formation is that these are dense systems in a crowded, extinguished part of the Milky Way, so observational analysis of the inner Galaxy GCs is difficult. Many of them are understudied, with basic parameters such as radial velocities and metallicities being undetermined, prompting new spectroscopic surveys to target inner Galaxy GCs (e.g., Saviane et al 2012;Dias et al 2016;Geisler et al 2021;Kunder et al 2021). The Milky Way Bulge extra-tidal star survey, MWBest, has the goal of spectroscopically identifying stripped globular cluster stars from inner Galaxy clusters.…”
Section: Introductionmentioning
confidence: 99%